The 'Histoire des Deux Indes': Reception, Historiography, Enlightenment - Kwiatkowski, Nicolás (História da Historiografia: International Journal of Theory and History of Historiography, 2024)
This article proposes an interpretation of the Histoire philosophique et politique des établissements et du commerce des Européens dans les deux Indes (1770) within the intellectual context of Enlightenment historiography. The first section describes the book, its contents, editions, authorship, and censorship. The second section provides a critical synthesis of the history of historiography on the work. The third section proposes an interpretation of the Histoire as an enlightened critique of colonialism and empire. A brief conclusion situates the book within a specific definition of the Enlightenment that accounts for its contradictions rather than attempting to overcome them.